PENGARUH PENGGUNAAN MODEL EXAMPLE NON EXAMPLE DALAM PEMBELAJARAN TEMATIK TERHADAP HASIL BELAJAR KETERAMPILAN MENULIS KELAS II - Kartika, Intan; Syambasril, Syambasril; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the effect of the use of the Example Non Example model on writing skills in class II 09 Pontianak Elementary School. The method used is an experimental method. Researchers used Quasi Experimental Design in the form of Nonequivalent Control Group Design. The population of this study consisted of two classes with a total of 65 students. The sampling technique used was purposive sampling, data collection techniques used were measurement techniques and documentary study techniques using data collection tools in the form of test essays in the pre-test and post-test in the experimental class and in the control class in class II Elementary School 09 pontianak West. Based on the analysis of the data obtained the average results of the experimental class post-test of 74.23 and post-test of the control class of 67.50 obtained tcount of 2.205 and ttable (Î± = 5% and dk = 30 + 30-2 = 58) of 2,002 because tcount> ttable, Ha is accepted. Based on the results of the calculation of the effect size (ES) obtained 0.61 So it can be concluded that there is an influence of the Example Non Example model on the writing skills of grade II students at 09 Pontianak Barat Elementary School.Â Keywords: Non Example Example Model, Writing Skills